Bidding in Construction Projects - Ayrancioglu, Oguz (2012)
Abstract In the construction industry, the selection of contractors is very challenging for both private companies and government. The most common method to choose contractor is bidding which has different types of models such as: design-bid-build, design-build, construction management and build-operate-transfer. For each of the model contractors would need various types of capabilities and competencies to be competitive. The risk of perception of the companies is also important to determine the competitiveness of the companies during the bidding process. International companies can use many strategies to increase their possibility of winning by submitting low bid. To achieve low bid strategy they would need local partnership, high tech solutions and innovative management. As the companies gain more responsibility in their awarded projects, they would try to finish the project in higher quality. In build-operate-transfer model contractors would consider their future operation profits so they will try to build best structure to avoid possible future problems in their own structure. Consequently, the trend is shifting to increase the responsibilities of the contractors and this will be developed by inventing new bidding models.